2019
DOI: 10.1016/j.compositesa.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the interfacial adhesion in basalt/epoxy composites by plasma polymerization

Abstract: In an attempt to improve mechanical properties of basalt fibre/epoxy composites, the present work provides a comparison between the effects of a commercial coupling agent, a thermal de-sizing treatment and a plasma polymerization process on the fibre/matrix interfacial strength. The different basalt fibres were characterized in terms of surface morphology, by FE-SEM observations, and chemical composition, performing FT-IR analysis. The interfacial adhesion has been investigated by single fibre fragmentation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Regarding the single basalt fiber reinforced composite (BF), the only apparent difference in the spectrum is the intensified peak at 2920 and 2850 cm −1 (C–H stretching). It was previously reported that the basalt fiber would exhibit a single absorbance peak at 1000 to 1200 cm −1 due to the Si-O-Si bond vibration and a minor peak at 2800 to 2900 cm −1 due to C–H stretching, which explains the intensified peak for the C–H stretching bands [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the single basalt fiber reinforced composite (BF), the only apparent difference in the spectrum is the intensified peak at 2920 and 2850 cm −1 (C–H stretching). It was previously reported that the basalt fiber would exhibit a single absorbance peak at 1000 to 1200 cm −1 due to the Si-O-Si bond vibration and a minor peak at 2800 to 2900 cm −1 due to C–H stretching, which explains the intensified peak for the C–H stretching bands [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a plain woven fabric (220 g/m 2 ), made of 100 % BCF (basalt continuous filament) roving. One basalt fibre has a nominal diameter of 13 m [40]. For all the composites, the same epoxy resin was used.…”
Section: Methodsmentioning
confidence: 99%
“…This coating process is characterized by the main advantage of providing a very thin film on the fiber reducing the amount of chemical needed with respect to other processes such as grafting and salinization. This technique was deeply studied by Seghini et al who investigated its effectiveness on flax yarns [64] and basalt fibers [65]. It was found out that PECVD improves significantly flax yarns adhesion with both vinyl ester and epoxy matrices and provides an adhesion quality superior to the one of the commercial fibers that are supplied with a commercial sizing.…”
Section: Surface Treatments For Interfacial Improvementmentioning
confidence: 99%